OPTIMIZING RESTORATIVE JUSTICE PROGRAM FOR THE BEST INTEREST OF THE CHILDREN IN REFORMING JUVENILE JUSTICE SYSTEM IN UTAH - Pratiwi, Cekli S (Legality : Jurnal Ilmiah Hukum, 2019)
This study examine first, to what extent the fully restorative justice system could be implemented in the Utah’s JJS and supported by the legislations so that the minor can enjoy a special protection while they still have the opportunity to participate actively with accountability in solving the problem without destroy their freedom and dignity and can bring more benefit to their best interest. Second, to what extent the right to legal counsel could help the minor to enjoy their constitutional rights as well as to seek a better solution of their problem. The research done by observing the review hearing, pre-trial, petition, trial at the Fourth Judicial District Courthouse Provo and the detention hearing at Slate Canyon Youth Center. The data is also collected from various secondary resources such as the Utah Statutes, the international and regional instruments. There is an opportunity for the JJS Utah county to shift from applying the partly to the fully RJP specially for truancy or misdemeanor cases and the right to access public defender should be automatically granted to the minors.